Overall survival with daratumumab, bortezomib, melphalan, and prednisone in newly diagnosed multiple myeloma (ALCYONE): a randomised, open-label, phase 3 trial. Issue 10218 (11th January 2020) - Mateos, Maria-Victoria; Cavo, Michele; Blade, Joan; Dimopoulos, Meletios A; Suzuki, Kenshi; Jakubowiak, Andrzej; Knop, Stefan; Doyen, Chantal; Lucio, Paulo; Nagy, Zsolt; Pour, Ludek; Cook, Mark; et al.
Summary: Background: Standard-of-care treatment for patients with newly diagnosed multiple myeloma includes combination therapies for patients who are not eligible for autologous stem-cell transplantation. At the primary analysis for progression-free survival of the phase 3 ALCYONE trial, progression-free survival was significantly longer with daratumumab in combination with bortezomib, melphalan, and prednisone (D-VMP) versus bortezomib, melphalan, and prednisone (VMP) alone in patients with transplant-ineligible, newly diagnosed multiple myeloma. Here we report updated efficacy and safety results from a prespecified, interim, overall survival analysis of ALCYONE with more than 36 months of follow-up. Methods: ALCYONE was a multicentre, randomised, open-label, active-controlled, phase 3 trial that enrolled patients between Feb 9, 2015, and July 14, 2016, at 162 sites in 25 countries across North America, South America, Europe, and the Asia-Pacific region. Patients were eligible for inclusion if they had newly diagnosed multiple myeloma and were ineligible for high-dose chemotherapy with autologous stem-cell transplantation, because of their age (≥65 years) or because of substantial comorbidities. Patients were randomly assigned in a 1:1 ratio and by permuted block randomisation to receive D-VMP or VMP. An interactive web-based randomisation system was used. Randomisation was stratified by International Staging System disease stage, geographical region, and age. There was no masking to treatment assignments. All patients received up to nine 6-week cycles of subcutaneous bortezomib (1·3 mg/m 2 of body surface area on days 1, 4, 8, 11, 22, 25, 29, and 32 of cycle one and on days 1, 8, 22, and 29 of cycles two through nine), oral melphalan (9 mg/m 2 once daily on days 1 through 4 of each cycle), and oral prednisone (60 mg/m 2 once daily on days 1 through 4 of each cycle). Patients in the D-VMP group also received intravenous daratumumab (16 mg/kg of bodyweight, once weekly during cycle one, once every 3 weeks in cycles two through nine, and once every 4 weeks thereafter as maintenance therapy until disease progression or unacceptable toxicity). The primary endpoint was progression-free survival, which has been reported previously. Results presented are from a prespecified interim analysis for overall survival. The primary analysis population (including for overall survival) was the intention-to-treat population of all patients who were randomly assigned to treatment. The safety population included patients who received any dose of study treatment. This trial is registered with ClinicalTrials.gov, NCT02195479 . Findings: 706 patients were randomly assigned to treatment groups (350 to the D-VMP group, 356 to the VMP group). At a median follow-up of 40·1 months (IQR 37·4–43·1), a significant benefit in overall survival was observed for the D-VMP group. The hazard ratio (HR) for death in the D-VMP group compared with the VMP group was 0·60 (95% CI 0·46–0·80; p=0·0003). The Kaplan-Meier estimate of the 36-month rate of overall survival was 78·0% (95% CI 73·2–82·0) in the D-VMP group and 67·9% (62·6–72·6) in the VMP group. Progression-free survival, the primary endpoint, remained significantly improved for the D-VMP group (HR 0·42 [0·34–0·51]; p<0·0001). The most frequent adverse events during maintenance daratumumab monotherapy in patients in the D-VMP group were respiratory infections (54 [19%] of 278 patients had upper respiratory tract infections; 42 [15%] had bronchitis, 34 [12%] had viral upper respiratory tract infections), cough (34 [12%]), and diarrhoea (28 [10%]). Interpretation: D-VMP prolonged overall survival in patients with newly diagnosed multiple myeloma who were ineligible for stem-cell transplantation. With more than 3 years of follow-up, the D-VMP group continued to show significant improvement in progression-free survival, with no new safety concerns. Funding: Janssen Research & Development.